SWOT Analysis of The Use of Digital Technology As an Innovation in Learning Media for Junior High School Students in Indonesia - Aprilliany Zahra Nur Azzalia Jacob; Erliza Septia Nagara; Ida Wahyu Wijayati; Feby Arief Nugroho; Miftahul Hadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is qualitative with a descriptive approach, which aims to describe each of the main topics covered in this article, including digital technology and learning media. The data used in this study is secondary data obtained by the researcher from various credible sources, including scientific articles, books, and credible websites. The data used was first collected, selected, corrected, analyzed using a SWOT analysis tool, and conclusions were drawn. The conclusion in this article show that the implementation or use of digital technology as a learning medium can be effective and beneficial for elementary school students due to its higher level of flexibility, greater enjoyment, and continued development. However, this implementation poses several threats and challenges, including excessive costs and the potential for misuse if not properly managed.